Extemporaneous formulations of oral paediatric medicines in Portuguese hospitals - Teixeira de Barros, Carla Maria (2015)
Study objectives: To characterise the drug use pattern and prescription profile of extemporaneous formulations in Portuguese hospitals. Methods: A cross-sectional study was performed over two months, in a convenience sample of six hospital pharmacy services. Results: A total of 52 extemporaneous formulations were dispensed to 303 paediatric patients. Most patients were children aged 1-12 years (49.2%). Premature babies and neonates accounted for 11.2%. Differences were not found between the proportion of male and female patients across the age groups (p = 0.785). Analysing the frequency distribution between patients aged under and over one year, and the patient's setting (i.e. inpatients or outpatients), it was verified that there was a high proportion of inpatients aged under one year (65.4%) compared with those aged over one year (34.6%) (p = 0.001). Eleven extemporaneous formulations were compounded by either crushing tablets or opening capsules, using the ingredients of the original medicine licensed for adults (63.6%), or from raw materials (36.4%). A total of 41 oral powders were prepared extemporaneously, of which the majority (39) were prepared from licensed tablets or capsules. The resulting powder was then redistributed in powder papers, each containing a smaller quantity. Folic acid powder papers were the most frequently prepared extemporaneously (14.7%). Where compounding is concerned, striking differences between hospitals were evident. In relation to four medicines formulated in all the hospitals studied, significant discrepancies were found in the compounding methods used. Conclusion: Although not the optimal solution, extemporaneous formulations allow the use of medicines in clinical practice when no other alternative exists. However, improvements have to be made, namely in the synchronisation of compounding practices and availability of paediatric formulations.